2021
DOI: 10.1210/clinem/dgab108
|View full text |Cite
|
Sign up to set email alerts
|

Elinzanetant (NT-814), a Neurokinin 1,3 Receptor Antagonist, Reduces Estradiol and Progesterone in Healthy Women

Abstract: Context The ideal therapy for endometriosis (EM) and uterine fibroids (UF) would suppress estrogenic drive to the endometrium and myometrium, whilst minimizing vasomotor symptoms and bone loss associated with current treatments. An integrated neurokinin-kisspeptin system involving Substance P and neurokinin B acting at the neurokinin (NK) receptors 1 and 3, respectively, modulates reproductive hormone secretion and represents a therapeutic target. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 64 publications
1
19
0
Order By: Relevance
“…Elinzanetant has recently been shown to dose‐dependently lower serum LH, oestradiol, and luteal‐phase progesterone in healthy women. At the highest dose tested, Elinzanetant prolonged the cycle length by a median of 7.0 days 107 . Collectively, these data demonstrate the involvement of NKB‐NK3R signalling in the physiological regulation of GnRH/LH secretion in women.…”
Section: Tacr3 and Tac3mentioning
confidence: 58%
See 1 more Smart Citation
“…Elinzanetant has recently been shown to dose‐dependently lower serum LH, oestradiol, and luteal‐phase progesterone in healthy women. At the highest dose tested, Elinzanetant prolonged the cycle length by a median of 7.0 days 107 . Collectively, these data demonstrate the involvement of NKB‐NK3R signalling in the physiological regulation of GnRH/LH secretion in women.…”
Section: Tacr3 and Tac3mentioning
confidence: 58%
“…At the highest dose tested, Elinzanetant prolonged the cycle length by a median of 7.0 days. 107 Collectively, these data demonstrate the involvement of NKB-NK3R signalling in the physiological regulation of GnRH/LH secretion in women.…”
Section: Clinical Studiesmentioning
confidence: 71%
“…108 Regarding safety, elinzanetant was well tolerated with no safety concerns identified during the study, nor any clinically relevant changes in blood pressure, heart rate or electrocardiogram parameters. 108 Therefore, further studies are now required in women with hormone driven disorders to examine the effects of NK1 and NK3 receptor antagonism.…”
Section: Manipulating Neurokinin B-signalling To Treat Uterine Fibroi...mentioning
confidence: 92%
“…107 A recent study investigated the effects of NK1 and NK3 receptor antagonism (elinzanetant: NT-814) on reproductive hormone secretion across two consecutive menstrual cycles in 33-healthy premenopausal women. 108 Following a baseline assessment cycle, women in the second cycle were randomised to once daily oral elinzanetant (40-120 mg) or placebo. This revealed that elinzanetant reduced oestradiol and progesterone levels in a dose-dependent manner without causing vasomotor symptoms.…”
Section: Manipulating Neurokinin B-signalling To Treat Uterine Fibroi...mentioning
confidence: 99%
See 1 more Smart Citation